Prenatal and postnatal exposure to pet ownership, blood pressure, and hypertension in children: the Seven Northeastern Cities study. Issue 2 (February 2017) - Xu, Shu-Li; Trevathan, Edwin; Qian, Zhengmin; Vivian, Elaina; Yang, Bo-Yi; Hu, Li-Wen; Zeng, Xiao-Wen; Li, Meng; Zhou, Yang; Qin, Xiao-Di; Bao, Wen-Wen; Yuan, Ping; et al.
Abstract : Objective: There is little information about how exposure to pets impacts blood pressure (BP) in children. The objective of the present study was to investigate the association between pet exposure and BP in children. Methods: A total of 9354 children, aged 5–17 years, from 24 elementary schools and 24 middle schools in the Seven Northeastern Cities were evaluated during 2012–2013. BP measurements were taken using a mercury sphygmomanometer. Hypertension in children was defined as having an average DBP or SBP in the 95th percentile or higher for the child's sex, age, and height. Results: Overall, 2127 of the 9354 participants (22.7%) had current exposures to pets, with 989 of all participants having dogs (10.6%). Pet exposure was negatively associated with hypertension and BP in men and women. Keeping dogs in the home was related to a significantly lower prevalence of hypertension in men [adjusted odds ratio (aOR) = 0.68; 95% confidence interval (CI): 0.49–0.94] and women (aOR = 0.66; 95% CI: 0.48–0.90). When the analysis was stratified by sex, in-utero exposure to pets was negatively associated with hypertension in men (aOR = 0.66; 95% CI: 0.45–0.97), and the associations with lower BP strengthened with higher levels of current pet exposure. As for BP, the associations between pet exposure and DBP were detected more in women; estimated decreases in mean DBP was 1.10 mmHg (95% CI: −1.75 to −0.45) for current pet exposure. Conclusion: Pet ownership reduces the odds of hypertension and elevated BP in children.